Pengembangan Sistem Informasi Akademik Sekolah Kepolisian berbasis Web (Studi Kasus: Setukpa Lemdiklat Polri Sukabumi) - Taruna Makki Satyanugraha; Achmad Arwan; Denny Sagita Rusdianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In the implementation of its learning activities, Setukpa Lemdiklat Polri Sukabumi is carried out by academic actors consisting of the Head of the Education and Training Section (KaBagdiklat), the Head of the Educators and Education Section (KaBagbingadik), and the Head of the Student Guidance Section (KaBagbimsis). At present, Setukpa Lemdiklat Polri Sukabumi is still using the conventional method for recording the value of each student in which the educator must record the scores of each student which are then entered in a sheet in the form of a table which is then submitted to the Head of the Education and Training Section (KaBagdiklat) in the form of hardcopy as a report. This can cause several problems for several reasons such as value data in tables that are prone to loss or table sheets that are prone to tearing or getting wet so that they cannot be reported to the Head of the Education and Training Section. Therefore, the authors developed a website-based academic information system in order to help students and educators of the Setukpa Lemdiklat Polri Sukabumi in monitoring students' academic grades. This research begins by describing the business processes that took place at Setukpa Lemdiklat Polri Sukabumi in order to find the required requirements, then design and implement them. From the results of system testing through unit testing, integration testing, and validation testing, the results are in accordance with system functionality. And from the results of the compatibility test results, the system can run well in several different browsers.